Inclusive processes of preschool education from the perspective of educational agents - Rubilar Bugueño, Fernanda (2021)
The article is carried out by the need to visualize the inclusive processes from the perspective of assistants, educators and directors belonging to the Integra Foundation, the National Board of Kindergartens (JUNJI) and gardens managed by the Municipality Vía Transferencia de Fondos (VTF) of the Copiapó commune of the Third Region of Chile, institutions that, by guidelines, are declared inclusive and recognized for working with the most vulnerable child population in Chile. The main objective of this research was to analyze the inclusive processes of preschool education in the Copiapó commune. He used the qualitative approach with an interpretive paradigm, through semi-structured interviews applied to nine educational agents in 2019, addressing meaning categories, learning methodologies, and impediments and facilitators. The results indicate that, although the educational agents use learning methodologies that favor the participation of each child, there is a conceptual lack of knowledge of inclusive education and disability. Regarding obstacles, there is little evidence of training on disability for educational agents, insufficient didactic material, outdated professional training and little infrastructural accessibility in the gardens. Regarding facilitators, external networks, enrollment management and the relationship of the educational agents with the family stand out. It is concluded that the incoherence of conceptualizations of the educational agents should provoke a training process that is oriented towards re-socialization. Similarly, the absence of a fund or program that encourages the implementation of adaptations in the infrastructure excludes children who require enrollment.